A Magnetic Valve at L1 Revealed in TESS Photometry of the Asynchronous Polar BY Cam - Mason Paul A; Littlefield Colin; Monroy Lorena C; Morales John F; Hakala Pasi; Garnavich Peter; Szkody Paula; Kennedy Mark R; Ramsay Gavin; Scaringi Simone (IOP Publishing Ltd, 2022)
We present TESS photometry of the asynchronous polar BY Cam, which undergoes a beat cycle between the 199.384 min white dwarf (WD) spin period and the 201.244 min orbital period. This results in changes in the flow of matter onto the WD. The TESS light curve covers 92% of the beat cycle once and 71% of the beat cycle twice. The strongest photometric signal, at 197.560 min, is ascribed to a side-band period. During times of light-curve stability, the photometry modulates at the spin frequency, supporting our WD spin-period identification. Both one-pole and two-pole accretion configurations repeat from one beat cycle to the next with clear and repeatable beat-phase-dependent intensity variations. To explain these, we propose the operation of a magnetic valve at L1. The magnetic valve modulates the mass-transfer rate, as evidenced by a factor of 5 variation in orbital-averaged intensity, over the course of the beat cycle in a repeatable manner. The accretion stream threading distance from the WD is also modulated at the beat period, because of the variation of the WD magnetic field with respect to the stream and because of changes in the mass transfer rate due to the operation of the magnetic valve. Changes in the threading distance result in significant shifts in the position of accreting spots around the beat cycle. As a consequence, only the faintest photometric minima allow for an accurate ephemeris determination. Three regions on the WD appear to receive most of the accretion flow, suggestive of a complex WD magnetic field.